Body weight support-Tai Chi footwork for balance of stroke survivors with fear of falling: A pilot randomized controlled trial. (November 2019) - Huang, ShangJun; Yu, XiaoMing; Lu, Yan; Qiao, Jun; Wang, HongLin; Jiang, Li-Ming; Wu, XuBo; Niu, WenXin
Abstract: Background and purpose : Balance impairment is the predominant risk factor for falls in stroke survivors. This study examined the effects of body weight support-Tai Chi (BWS-TC) footwork on balance control among stroke survivors with fear of falling (FOF). Materials and methods: Twenty-eight stroke survivors with FOF were randomly allocated to either control or BWS-TC groups. Those in BWS-TC underwent Tai Chi training for 12 weeks. Outcomes were assessed in all participants by evaluation of the limits of stability test, modified clinical test of sensory integration of balance, fall risk index, and Fugl-Meyer assessment of lower limbs at baseline and 12 weeks. Results: The BWS-TC group displayed significant enhancement in dynamic control and vestibular and somatosensory integration. Conclusion: BWS-TC may enhance dynamic control and sensory integration of balance and reduce the risk of fall in stroke survivors with FOF. Highlights: The BWS-TC training significantly enhanced the ability of dynamic balance control. The sensory integration of balance was enhanced after 12-week BWS-TC intervention. Lower limb function was enhanced after 12-week BWS-TC intervention. The fall risk of stroke patients was reduced by 12-weeks of BWS-TC intervention.